2015
DOI: 10.1155/2015/691071
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism in Children and Adolescents: Is It Clinically Relevant?

Abstract: Although subclinical hypothyroidism (SH) is a common clinical problem, its diagnosis tends to be incidental. According to the definition, it should be asymptomatic, only detectable by screening. The presence or coincidence of any symptoms leads to L-thyroxine treatment. The clinical presentation, especially in younger patients with subclinical hypothyroidism, is still under dispute. Accordingly, the aim of this paper was to review the literature from the past seven years. The literature search identified 1,594… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…1). Although thyroid volume can increase during puberty (1920), and thyroid hormone requirements may increase during the pubertal growth spurt (2122), thyroid dysfunction can develop irrespective of pubertal onset. Furthermore, a previous prospective study with iso-NAHT patients reported that normalization of TSH concentrations was less evident in prepubertal patients than pubertal patients (8).…”
Section: Discussionmentioning
confidence: 99%
“…1). Although thyroid volume can increase during puberty (1920), and thyroid hormone requirements may increase during the pubertal growth spurt (2122), thyroid dysfunction can develop irrespective of pubertal onset. Furthermore, a previous prospective study with iso-NAHT patients reported that normalization of TSH concentrations was less evident in prepubertal patients than pubertal patients (8).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority of these patients (61.9%) spontaneously normalized over time their TSH values, and only a small minority (11.9%) became overtly hypothyroid. Nevertheless, it has to be pointed out that almost a quarter of group A girls required L-T 4 treatment during the observation period, which underlines the importance of a biochemical follow-up, even in the children with idiopathic and mild SH (33,36). According to the recent guidelines of the European Thyroid Association, in these children monitoring can be performed every 12 months due to the low risk of progression (33).…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypothyroidism (SCH) is defined biochemically as an elevated thyroid stimulating hormone (TSH) in the presence of a normal serum free thyroxine (T4). While most experts recommend levothyroxine therapy for subclinical hypothyroidism with TSH greater than 10 mIU/L, there is lack of consensus on whether mild SCH with TSH levels between 5 and 10 mIU/L should be treated . Several studies in adults demonstrate an association between elevated TSH and total and low density lipoprotein(LDL) cholesterol concentrations .…”
Section: Introductionmentioning
confidence: 99%